REINTERPRETATION THE HADITH ON MARRIAGE PREFERENCES FROM GADAMER'S HERMENEUTICS PERSPECTIVE: Integrating Textual Meaning and Contemporary Social Relevance - PK, Moh. Nurun Alan Nurin; Qudsia, Miatul; Irfani, Muhammad Syahru (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2025)
The hadith regarding preferences in choosing a life partner, which states, "Women are married for four reasons..." is often interpreted in a partial and hierarchical manner, where physical aspects such as beauty, wealth, and lineage are positioned equally or even above religious values. This textual-literal interpretation tends to reproduce patriarchal norms and disregards the historical context in which the hadith was revealed. This study aims to reinterpret the hadith through the philosophical hermeneutics of Hans-Georg Gadamer, emphasizing pre-understanding and the fusion of horizons between the text and the reader. A qualitative-critical approach is employed, drawing on classical (turāth) and contemporary literature as the foundation for analysis. The findings reveal that religion, as mentioned in the hadith, is not merely one of four equal considerations but represents a normative critique against the materialistic and status-driven tendencies of Arab society at the time. Non-physical criteria such as moral integrity, responsibility, and mutual respect are identified as the essence of religious values to be prioritized. Through Gadamerian hermeneutics, this hadith can be contextualized as an ethical guideline for establishing marital relationships that are balanced, just, and free from patriarchal domination. Thus, this study offers an alternative, reflective, and contextually grounded interpretation of the hadith, reaffirming the importance of religious values in contemporary social practice.